Analisis Interaksionis Simbolik dalam Konteks Proses Pembelajaran (Literatur Review) - Amalina Nabila (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Symbolic interactionism is an approach that examines how symbols and meanings are created through interactions between individuals within a learning context. This approach explores how individuals use symbols to communicate, interact, and understand the world around them. In the context of the learning process, symbolic interactionist analysis can provide a deep understanding of how learning occurs through interactions between teachers and students, as well as among students themselves. Through this analysis, we can observe how symbols such as language, gestures, and expressions are used to communicate ideas and concepts being taught in the classroom. Additionally, symbolic interactionist analysis can also help us understand how individuals construct their identities within the learning environment. In the modern era of education, the interaction between teachers and students has become one of the crucial aspects of the learning process. Through social interaction and the use of symbols, individuals can shape their perceptions of themselves and how they are viewed by others. This can affect their motivation and engagement in learning. Thus, symbolic interactionist analysis offers valuable insights into understanding the learning process and how interactions between individuals play a key role in the construction of meaning and understanding. Through this understanding, we can improve the quality of learning and provide more meaningful learning experiences for students. Communication does not only occur through words but also through nonverbal communication, including facial expressions, body movements, and other gestures. Therefore, this study aims to analyze how symbolic interactionism plays a role in learning and how nonverbal communication influences the dynamics of classroom interaction.